Pain as the only symptom of cervical artery dissection. Issue 9 (4th July 2006) - Arnold, M; Cumurciuc, R; Stapf, C; Favrole, P; Berthet, K; Bousser, M-G
Abstract : Background: Headache or neck pain is a frequent symptom of spontaneous cervical artery dissection (sCAD). Patients and methods: Patients were drawn from an ongoing hospital-based registry of consecutive cases diagnosed with sCAD. Only patients with isolated pain were included in this series. Pain topography, dynamics, severity and quality, imaging findings and outcome were analysed. Results: 20 of 245 (8%) patients with sCAD presented with pain as the only symptom (mean (SD) age 39 (8) years; 14 (70%) women). Of them, 12 had vertebral artery dissection, 3 had internal carotid dissection and 5 had multiple dissections. The median delay from symptom onset to diagnosis was 7 days (range 4 h to 29 days). 6 patients presented with headache, 2 with neck pain and 12 with both. Onset of headache was progressive in 6, acute in 8 and thunderclap-type in 4 patients; neck pain was progressive in 7 and acute in 7. Headache was throbbing in 13 and constrictive in 5 patients; neck pain was throbbing in 4 and constrictive in 10. Pain was unilateral in 11 and bilateral in 9. Pain was different from earlier episodes in all but one case. All patients were pain free at 3 months. Conclusion: Pain may be the only symptom in sCAD, even when multiple arteries are dissected. Pain topography, dynamics, quality and intensity were heterogeneous. Data from this study lend support to recommendations favouring imaging studies of the cervical arteries in patients with new-onset unexplained headache or neck pain.